DENR-MCT-1 promotes translation re-initiation downstream of uORFs to control tissue growth. - Schleich, S.; Strassburger, K.; Janiesch, P.C.; Koledachkina, T.; Miller, K.K.; Haneke, K.; Cheng, Y.S.; Küchler, K.; Stoecklin, G.; Duncan, K.E.; Teleman, A.A. (Nature, 2014)
During cap-dependent eukaryotic translation initiation, ribosomes scan messenger RNA from the 5' end to the first AUG start codon with favourable sequence context. For many mRNAs this AUG belongs to a short upstream open reading frame (uORF), and translation of the main downstream ORF requires re-initiation, an incompletely understood process. Re-initiation is thought to involve the same factors as standard initiation. It is unknown whether any factors specifically affect translation re-initiation without affecting standard cap-dependent translation. Here we uncover the non-canonical initiation factors density regulated protein (DENR) and multiple copies in T-cell lymphoma-1 (MCT-1; also called MCTS1 in humans) as the first selective regulators of eukaryotic re-initiation. mRNAs containing upstream ORFs with strong Kozak sequences selectively require DENR-MCT-1 for their proper translation, yielding a novel class of mRNAs that can be co-regulated and that is enriched for regulatory proteins such as oncogenic kinases. Collectively, our data reveal that cells have a previously unappreciated translational control system with a key role in supporting proliferation and tissue growth.